Nutrigenomics – perspectives from registered dietitians: a report from the Quebec‐wide e‐consultation on nutrigenomics among registered dietitians. Issue 4 (6th January 2014) - Cormier, H.; Tremblay, B. L.; Paradis, A.‐M.; Garneau, V.; Desroches, S.; Robitaille, J.; Vohl, M.‐C.
Abstract Background Not all healthcare professionals are familiar with nutrigenomics. However, they recognise that nutrigenomics has great potential for the development of preventive health approaches. The present study aimed to provide an overall picture of the current situation about nutrigenomics in the practice of registered dietitians (RDs) from the province of Quebec (Canada). Methods Three hundred and seventy‐three RDs members of the Ordre professionnel des diététistes du Québec completed an online survey that included 34 questions, most of which were closed‐ended questions. Results Overall, 76.9% of RDs knew about nutrigenomics. Among RDs with <5 years of experience, 49.2% knew about genetic testing related to nutrition compared to 11.7% for RDs with over 25 years of experience. Currently, 75.9% of RDs working in clinical nutrition in the public sector consider that they do not have the basic knowledge to integrate nutrigenomics in their practice compared to 62.9% for RDs in private practice. When asked about main limitations of genetic testing related to nutrition, RDs considered that genetic testing does not consider the other determinants of health, that genetic testing and their results have poor accuracy, and that there is a lack of scientific evidence. Concerns remained about ethical and legal aspects and its difficult application as a result of poor understanding and/or interpretation by professionals and/or customers. The high costs of these tests were also noted as a limitation. Conclusions Registered dietitians know and are interested in nutrigenomics, especially those with less experience, although they do not feel adequately qualified to integrate findings from nutrigenomics into their practice.